2009
DOI: 10.1007/s10800-009-9807-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of some antiscalants as corrosion inhibitor for industrial cooling water system

Abstract: In order to study synergistic effect, various combinations of antiscalants 1-hydroxyethane-1,1-diphosphonic acid (HEDP), sodium hexametaphosphate (SHMP), sodium tripolyphosphate (STPP), and trisodium phosphate (TSP), were investigated as corrosion inhibitors for carbon steel. Corrosion rate and percentage inhibition efficiency of various combinations of antiscalants as corrosion inhibitors (20/80, 40/60, 60/40, 50/50, 80/20, and 100 ppm of different combinations of HEDP, SHMP, STPP, and TSP) in synthetic cooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…Meanwhile, the peaks at d 5 4.20 ppm proved the existence of carbonyl groups. All of these suggested that the AOH groups in PEG 8 were entirely transformed into AOC(@O)CH@CHCOOH and PEG 8 The double-bond adsorption peaks at d 5 6.37 ppm in Figure 1(b) completely disappeared in Figure 1(c); we concluded that free-radical polymerization between PEG 8 DMA and AA occurred.…”
Section: Static Scale Inhibition Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…Meanwhile, the peaks at d 5 4.20 ppm proved the existence of carbonyl groups. All of these suggested that the AOH groups in PEG 8 were entirely transformed into AOC(@O)CH@CHCOOH and PEG 8 The double-bond adsorption peaks at d 5 6.37 ppm in Figure 1(b) completely disappeared in Figure 1(c); we concluded that free-radical polymerization between PEG 8 DMA and AA occurred.…”
Section: Static Scale Inhibition Methodsmentioning
confidence: 77%
“…To gain a better understanding of the stand or fall of the PEG 8 DMA/AA inhibition power, the effects of PEG 8 Figure 3.…”
Section: Comparison Of Inhibition Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphonate groups were inserted into 2-aminobenzimidazole to develop such inhibitor with an improved corrosion inhibition as well as a high scaling inhibition efficiency. In fact, phosphonate is known as an anti-scaling group [30][31][32]. This threshold inhibitor is added to aquatic media even with high calcium ion concentration and disrupts the formation of precipitates by means of adsorption onto crystal growth sites [33].…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, íons fosfato vêm sendo empregados há mais de um século como meio para proteger superfícies metálicas dos efeitos da corrosão, seja na forma de banhos fosfatizantes [40], como na forma de sais aplicados como inibidores de corrosão para diversos meios e materiais metálicos [41] [42] [43].…”
Section: Inibidores à Base De Fosfatounclassified